ANALYSIS OF FACTORS AFFECTING CUSTOMER INTEREST IN CHOOSING RAHN PRODUCTS AT SHARIA PAWNSHOPS IN ACEH PROVINCE - Puteh, Anwar; Rasyidin, M.; Authar ND, Muhammad; Mawaddah, Nurul (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study examines the effect of Promotion, Ujrah Rates and Fund Disbursement Procedures on Customer Interest in Choosing Rahn Products at Sharia Pawnshops in Aceh Province. This study uses primary data obtained by distributing questionnaires to selected customers using a non-probability sampling method. The data analysis method used multiple linear regression analysis. The results showed that the promotion variable, and the procedure for disbursing funds had a positive and significant effect on customer interest in choosing Rahn's products at Pegadaian Syariah in Aceh Province. Meanwhile, the ujtrah rate variable has a negative and significant effect on customer interest in choosing Rahn's products. Recommendations from this research are expected that the Aceh Sharia Pawnshop can increase promotion as a means of introducing products to the public. Meanwhile, the ujrah tariff rate is reconsidered (to be lowered) and in terms of disbursement of funds it can be maintained in order to increase public interest in using Rahn's products at Sharia Pawnshops in the future.